AIMS students mobility programme in Thailand: empirical evidence on the wider sphere of students’ perceptions - Isma Rosila Ismail,; Fiffy Hanisdah Saikim,; Noor Zaitun Yahaya,; Tan, Min Pau; Yusof Shuaib Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The number of students participating in Asian International Mobility for Students (AIMS) programs has increased enormously over the years. The reasons are diverse and may range from personal growth to better employability prospects, together with improvement in foreign language skills and intercultural awareness. AIMS programs receive generous funding from Bahagian Education Malaysia (BEM) of the Ministry of Education, Malaysia, therefore their outcomes should be measured and evaluated. This paper focuses on students’ experiences and their lesson learned as an alumnus of AIMS program. Reports submitted by the students were analysed using Leximancer and Spider-web Configuration. The content analysis done using Leximancer shows nine variables that are “orientation”, “Thailand”, “internship”, “training”, “water”, “people”, “food”, “excursions” and “important” that according to the students are of important in terms of their experiences and satisfaction of the AIMS program. While the Spider-web Configuration shows five items that make the AIMS program worth it and pays off for students to participate. In particular, the students’ international experiences caused them to reflect deeply on matters of different styles of education, gain valuable knowledge in their major and develop communication skills. In addition, they could live independently in another culture for an extended period, develop confidence and self-understanding, learn another language, gain a unique cultural experience and make new lifelong friends. The students’ reflections also offer the university sector some points to consider with respect to student mobility programs, particularly in how participants are supported in interpreting their overseas experience.